Venomous Terrestrial Snakes of Malaysia: Their Identity and Biology - Das, Indraneil; Norhayati, Ahmed; Lim, Boo Liat (Springer Netherlands, 2015)
This article presents an overview of the identity and biology of the venomous terrestrial snakes of Malaysia, from Peninsular Malaysia and the Bornean states of Sabah and Sarawak. Two families account for a majority of venomous snakes that are of medical significance – the Elapidae (cobras, kraits, and coral snakes) and Viperidae (vipers and pit vipers). Certain members of the Colubridae are capable of giving life-threatening bites to humans (especially species of Rhabdophis), but little is known of the Malaysian species of the genus. A number of other species in the family have been implicated with human envenomation, although little objective evaluation appears to have been published. This article synthesizes data on the identification, distribution, and conservation of these snakes; provide colored images of every recognized species and subspecies of venomous terrestrial snakes of the families Elapidae and Viperidae known to occur in the country; and conclude with strategies to improve knowledge of the snakes of the country.